Influence of Hatch Strategy on Crystallographic Texture Evolution, Mechanical Anisotropy of Laser Beam Powder Bed Fused S316L Steel. Issue 7 (12th August 2022) - Bodner, Sabine C.; Hlushko, Kostyantin; Kutleša, Kevin; Todt, Juraj; Renk, Oliver; Meindlhumer, Michael; Resch, Florian; Nielsen, Marc-André; Keckes, Jozef; Eckert, Jürgen
Abstract : The correlations between process conditions, microstructure, and mechanical properties of additively manufactured components are not fully understood yet. In this contribution, three different hatch strategies are used to fabricate rod‐like samples from S316L stainless steel, which are further investigated using synchrotron diffraction, optical microscopy, and tensile tests. The results indicate the presence of ⟨110⟩ biaxial and fiber textures, whose sharpness depends on the applied hatch strategy. Mechanical tests reveal a strong correlation of the samples' response to the observed anisotropy in the plane perpendicular to the build direction. Even though the average yield and ultimate tensile strengths of around 475 and 500 MPa, respectively, do not differ significantly, the stress–strain behavior can be correlated with the observed in‐plane anisotropy. Particularly, twinning‐induced plasticity, a distinct increase of the work hardening rate at larger strains and elliptical necking are observed in some samples with biaxial (Goss) texture. These findings indicate that texture design by means of applying dedicated hatch strategies can be used to effectively tune the multiaxial deformation behavior of components produced by laser powder bed fusion. Abstract : Three hatch strategies—plane, stripe, and chess—applied during laser beam powder bed fusion of stainless steel S316L lead to the formation of different preferred crystal orientations in tensile samples. The samples exhibit a different deformation behavior during tensile loading which can be correlated with the hatch strategies and can be used to tailor mechanical properties of additively manufactured parts.